2015
DOI: 10.4300/jgme-d-14-00364.1
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Cesarean Operative Time Following Institution of the 80-Hour Workweek

Abstract: Background In 2003, the Accreditation Council for Graduate Medical Education limited resident duty hours to 80 hours per week. More than a decade later, the effect of the limits on resident clinical competence is not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…These facts are consistent with an increase in the average number of cesarean sections per ObGyn resident from 191.8 in 2002-2003 to 233.4 in 2012-2013, while volumes of vaginal, forceps, and vacuum deliveries, and amniocentesis decreased [11]. Nevertheless, operative time per CD increased by a mean of 16.3 minutes from 2003-2004 to 2010-2011, p<0.001, attributable to declining trainee skill and/or increasing surgical complexity [12]. It is known that high volume surgeons can have significantly lower complication rates than low volume surgeons, p<0.001 [13].…”
Section: Introductionsupporting
confidence: 70%
“…These facts are consistent with an increase in the average number of cesarean sections per ObGyn resident from 191.8 in 2002-2003 to 233.4 in 2012-2013, while volumes of vaginal, forceps, and vacuum deliveries, and amniocentesis decreased [11]. Nevertheless, operative time per CD increased by a mean of 16.3 minutes from 2003-2004 to 2010-2011, p<0.001, attributable to declining trainee skill and/or increasing surgical complexity [12]. It is known that high volume surgeons can have significantly lower complication rates than low volume surgeons, p<0.001 [13].…”
Section: Introductionsupporting
confidence: 70%
“…There is a reported lack of confidence among gynaecology graduates to perform the breadth of procedures in the specialty . The reduced number of real‐procedure opportunities for teaching and practise has hampered surgical training in gynaecology . Simulation allows additional opportunities for surgical training and is being increasingly used as an adjunct to traditional methods .…”
Section: Introductionmentioning
confidence: 99%
“…This must be balanced with safe working hours, providing continuity of patient care, training standards, teaching opportunities, professional identity and time spent with family/pursuing interests outside of work. While the restriction of working hours internationally has not appeared to significantly impact on patient outcomes there is a concern that reduced hours may adversely affect training, particularly in skill‐based specialties such as O&G . A previous study of RANZCOG trainees reported a lack of confidence in surgical skills at the completion of training .…”
Section: Discussionmentioning
confidence: 99%